Legal Protection of Indonesian Migrant Workers (TKI) Overseas (Case Study of BP3TKI North Sumatera Province) - Vinna Dinda Kemala; Eny Kusdarini (Universitas Lampung, 2020)
Efforts to deliver overseas labour are considered effective to reduce the high unemployment rate in Indonesia. However, the higher the labour interest that wants to become migrant workers, the more cases experienced by Indonesian Migrant Workers (Tenaga Kerja Indonesia or TKI) abroad such as violence, rape, and wages that are not given during work. The low level of education of migrant workers is considered to be one of the main factors of the violence experienced by TKI. Protection against TKI working abroad has been governed by law No. 18 of 2017 on the protection of Indonesian migrant workers. The Indonesian Manpower Placement and Protection Agency (BP3TKI) is one of three institutions responsible for protecting the TKI working overseas. The purpose of this research is to further the broader explanation of the legal protection of Indonesian migrant workers abroad, conducted by BP3TKI in North Sumatera province. The method used in this study is a qualitative descriptive method consisting of interviews, documentation, and library studies. The results of this study indicate BP3TKI has carried out its duties based on Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers. In carrying out its duties, there are several factors and obstacles faced by BP3TKI to provide maximum legal protection to Indonesian migrant workers.